Parataxis, hypotaxis, and subordination in Brazilian Sign Language: a brief introduction - Gonçalves Carneiro, Bruno; Ishac Brandão El Khouri, José; Cristina Santos, Thamara; Roberto Ludwig , Carlos (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2024)
Clause articulation is a grammatical strategy found in all-natural languages. This phenomenon gives rise to complex constructions that manifest in a continuous gradient (parataxis – hypotaxis – embedding) from integrating syntactic, semantic, and pragmatic levels of the language in use. The present study is guided by a functionalist perspective of language and aims to describe some articulation processes of sentences in Brazilian Sign Language (Libras). Regarding the Libras data, we noticed that juxtaposition, conjunctions, facial expressions, prolonged head nod, head nod linked to ALREADY mouthing, trunk displacement, and the maintenance of the non-dominant hand (buoy) could play a role. An essential role in the articulation of clauses or, at least, in the cohesion of the sentence.